2021
DOI: 10.1371/journal.pone.0261684
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-dose pirfenidone on survival and lung function decline in patients with idiopathic pulmonary fibrosis (IPF): Results from a real-world study

Abstract: Background Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive fibrosing interstitial pneumonia of unknown etiology. In several randomized clinical trials, and in the clinical practice, pirfenidone is used to effectively and safely treat IPF. However, sometimes it is difficult to use the dose of pirfenidone used in clinical trials. This study evaluated the effects of low-dose pirfenidone on IPF disease progression and patient survival in the real-world. Methods This retrospective, observational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
(49 reference statements)
2
8
0
Order By: Relevance
“…Of the 16 studies reviewed, we found that 14 studies were detected with presence of ITB based on the ITB checklist, while there were insufficient data for assessment of two others. This is consistent with a recently published Letter to Editor (26) that summarized observational studies reporting the effectiveness of antifibrotic therapy on mortality of IPF and identified 14 studies (16-19, 35,41,42,44,45,[53][54][55][56][57] presenting ITB. Compared to a previous study (26), we have included more studies and have provided more detailed information by using the ITB checklist and conducting a simulation study to identify and account for ITB in IPF studies.…”
Section: Identification Of Itbsupporting
confidence: 88%
“…Of the 16 studies reviewed, we found that 14 studies were detected with presence of ITB based on the ITB checklist, while there were insufficient data for assessment of two others. This is consistent with a recently published Letter to Editor (26) that summarized observational studies reporting the effectiveness of antifibrotic therapy on mortality of IPF and identified 14 studies (16-19, 35,41,42,44,45,[53][54][55][56][57] presenting ITB. Compared to a previous study (26), we have included more studies and have provided more detailed information by using the ITB checklist and conducting a simulation study to identify and account for ITB in IPF studies.…”
Section: Identification Of Itbsupporting
confidence: 88%
“…Another phase III trial in Japan reported a significant difference in vital capacity (approximately 0.07 L) between the high-dose (1800 mg/day) and placebo groups (p = 0.0416) and a significant difference in vital capacity (approximately 0.09 L) between the low-dose (1200 mg/day) and placebo groups (p = 0.0394), suggesting that low-dose pirfenidone is effective [12]. A study assessing real-world pirfenidone data in South Korea reported that relatively a low dose of pirfenidone (�1200 mg/day) can have an effect on pulmonary function decline [14,15]. In our study, we compared changes in FVC and DLCO between the standard and low-dose groups and found no significant difference in efficacy with dose, which is comparable to the findings of previous studies.…”
Section: Plos Onementioning
confidence: 99%
“…Although some studies have reported that low-dose pirfenidone is not inferior to a standard dose [12,14,15], there are few reports focused on the side effects associated with pirfenidone and reduced doses. Thus, we aimed to investigate clinical characteristics of and factors associated with dose reduction of pirfenidone in a real-world setting.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a systematic review and meta-analysis of RCTs also indicated that Pirfenidone treatment was associated with a longer progression-free-survival and a lower incidence of acute exacerbation (Wu et al, 2021). In the real-world practice, Pirfenidone also provided beneficial effects on survival and pulmonary function decline (Lee et al, 2021). Moreover, A post hoc analysis of ASCEND and CAPACITY program suggested a clinically relevant benefit of Pirfenidone in IPF patients with more advanced lung function impairment (Nathan et al, 2019).…”
Section: Pirfenidonementioning
confidence: 99%